Neural Mechanisms of Choice Diversification - Couwenberg, Linda E.; Boksem, Maarten A. S.; Sanfey, Alan G.; Smidts, Ale (Frontiers in Neuroscience, 2020)
When asked to select several options at once, people tend to choose a greater diversity of items than when they are asked to make these selections one at a time. Using functional magnetic resonance imaging, we provide novel insight into the neural mechanisms underlying diversification in portfolio choices. We found that, as participants made multiple selections from a menu of different options, the current state of their choice portfolio (i.e., the previously selected options) dynamically modulates activity in the neural valuation system in response to the options under evaluation. More specifically, we found that activity in the ventral striatum decreases when the option has already been selected (‘satiation’), while activity in the ventromedial prefrontal cortex increases when other options have previously been selected (‘novelty-seeking’). Our findings reveal two processes that drive diversification in portfolio choices, and suggest that the context of previous selections strongly impacts how the brain evaluates current choice options.